2016
DOI: 10.2147/oarrr.s113288
|View full text |Cite
|
Sign up to set email alerts
|

Repository corticotropin injection in patients with refractory psoriatic arthritis: a case series

Abstract: PurposeAlthough numerous treatment options are available for patients with psoriatic arthritis (PsA), a need for effective and tolerable treatments remains for patients with refractory disease who have failed previous therapies and continue to experience tender and/or swollen joints, pain, and disease activity. Repository corticotropin injection (RCI) is believed to produce steroidogenic, steroid-independent, anti-inflammatory, and immunomodulatory effects in patients with rheumatic disorders, such as PsA. Lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Unfortunately, ACTH lacks modern data and new randomized controlled trials (RCTs) supporting its clinical significance in axial spondylarthritis. An exception would be a case series by Brown et al [64], where they treated 9 difficult-to-treat psA patients with CI and noticed some improvement in skin and joint disease.…”
Section: Acth and Rheumatic Diseasementioning
confidence: 99%
“…Unfortunately, ACTH lacks modern data and new randomized controlled trials (RCTs) supporting its clinical significance in axial spondylarthritis. An exception would be a case series by Brown et al [64], where they treated 9 difficult-to-treat psA patients with CI and noticed some improvement in skin and joint disease.…”
Section: Acth and Rheumatic Diseasementioning
confidence: 99%
“…Real-world experience with RCI has been reported in case series in patients with psoriatic arthritis and SLE [ 17 , 18 ]; in retrospective chart reviews in patients with sarcoidosis, RA, various rheumatologic diseases, uveitis, SLE, and dermatomyositis/polymyositis (DM/PM) [ 7 , 19 22 ]; and in claims database analyses in patients with RA, other rheumatologic conditions, and SLE [ 23 , 24 ]. These types of studies show that in routine clinical practice, patients who receive RCI tend to have difficult-to-treat disease and have tried multiple available alternative treatments without successful resolution of symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Recent progress in understanding the effects of RCI in modulating immune responses has led to increased interest in RCI as a therapeutic choice [2]. Clinical trials and retrospective case series have found RCI to be effective for reducing disease activity and signs/symptoms as well as improving functional status in patients with RA, PsA, DM/PM, and SLE [3][4][5][6][7][8][9][10][11][12]. Claims data studies that examined medical resource use (MRU) relating to rheumatologic disorders reported that RCI treatment was associated with reduced health care utilization [13,14].…”
Section: Introductionmentioning
confidence: 99%